Animal theologians - Linzey, Andrew; Linzey, Clair ca. 20./21. Jh. (Oxford University Press, 2023)
"Many people who have thought about God have not thought about animals, or about the relationship between the two. But some have, and they have been among some of the most celebrated religious thinkers, including Michel de Montaigne, Thomas Tryon, John Wesley, John Ruskin, Leo Tolstoy, Mohandas K. Gandhi, Albert Schweitzer, and Paul Tillich. This volume comprises 24 scholarly studies that detail challenges to the dominant anthropocentrism of most religious traditions. The editors have brought together Jewish, Unitarian, Christian, transcendentalist, Muslim, Hindu, Dissenting, deist, and Quaker voices, all offering unique theological perspectives that reverse the neglect of the nonhuman. This work is an act of reclaiming different traditions for animals by recovering lost voices"--